HISTORIA AMBIENTAL DE LA REGIÓN PUNO - Huanca Excelmes, Irene (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
The author develops the environmental history of Puno since the independence of Peru, explains the reason for history in the environmental discipline, for this he addresses the ethnic groups of Lake Titicaca, the evolution of the nature of the natural heritage, finally concludes that Our region has the pending task of conserving its natural heritage through the execution of the Report on priority areas for conservation in the Puno region and that it is necessary to promote the joint management proposal such as the Vilcambamba-amboro biological corridor according to the Bolivian Center for multidisciplinary studies.